In Vitro Probiotic Characterization of Lactiplantibacillus plantarum Strains Isolated from Traditional Fermented Dockounou Paste - Kouadio, Natia Joseph; Zady, Alalet Luc Olivier; Kra, Kouassi Aboutou Séverin; Diguță, Filofteia Camelia; Niamke, Sébastien; Matei, Florentina (MDPI AG, 2024)
This study aimed to evaluate the probiotic properties of 10 lactic acid bacteria (LAB) isolated from artisanal fermented plantain dockounou paste. A preliminary characterization of the LAB isolates was performed based on phenotypic and several biochemical properties, which was subsequently confirmed through 16S rRNA gene sequencing analysis, indicating that these isolates belonged to the species Lactiplantibacillus plantarum. With regard to safety criteria, the strains exhibited no alpha or beta hemolysis activity. Nevertheless, the majority of LAB strains demonstrated high sensitivity to the antibiotics tested. The results demonstrated that the majority of the strains exhibited remarkably high survival rates under simulated gastrointestinal conditions, such as pH = 1.5 (81.18–98.15%), 0.3% bile salts (68.62–100.89%), 0.4% phenol (40.59–128.24%), as well as 0.1% pepsin and pH = 2.5 (88.54–99.78%). The LAB strains demonstrated elevated levels of cell surface properties, indicative of the presence of a considerable defensive mechanism against pathogens. Intact LAB cells exhibited significant antioxidant abilities (48.18–83.58%). They also demonstrated a pronounced inhibitory effect on the growth of foodborne pathogens. Enzyme pattern analysis revealed that the LAB isolates produced both proteases and cellulases, as well as pectinase and/or amylase activity. The potential of the L. plantarum strains FS43, FS44, and FS48, as indicated by the results obtained from the standard in vitro assays, makes them suitable for further study as potential probiotics.
Keywords: fermented plantain dockounou paste; Lactiplantibacillus plantarum; probiotic properties; health benefits